A Case Study of MSMEs and Their Credit Repayment Pattern - Kumar, Abhishek; Goel, Sachin (Journal of Commerce and Trade, 2019)
A Country like India can only sustain its development on these sectors. In the recent past, the changes that took place are evident enough that the MSMEs have again gained its lost paradise. This sector again proved to be a significant one in providing pace to rapidly increasing Indian Mass and the Economy. This is because of their capacity to promote entrepreneurial skills, and their ability to be swiftly adaptable to a changing market, and to generate new jobs. The relationship between entrepreneur characteristics and firm repayment performance has received a lot of focus in recent times. The factors which form the character and behaviour of the entrepreneur are crucial internal capacities that impact on firm repayment performance as the rate of MSMEs failure in developing countries as well as developed countries is alarming. But, it is very important to quote here that the most of the promoters of MSMEs face financial crunch throughout the country. Finance has been an important ingredient in MSMEs development as well as national development. The implications of this study are that specific policy measures are necessary to encourage the many well trained but unemployed young people to engage in businesses. Additionally it also implies that specific training programs are necessary to equip the practitioners with necessary theoretical and practical capacities to enhance performance of their firms. Classification-JEL : G 01, G 32, L 10.